2017
DOI: 10.3201/eid2306.161607
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Hantavirus in Field Voles, Northern England

Abstract: We report a PCR survey of hantavirus infection in an extensive field vole (Microtus agrestis) population present in the Kielder Forest, northern England. A Tatenale virus–like lineage was frequently detected (≈17% prevalence) in liver tissue. Lineages genetically similar to Tatenale virus are likely to be endemic in northern England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Later, TULV was also isolated from the vole samples collected in the central European countries [ 59 ]. A novel vole-associated hantavirus related to TULV and PUUV, Tatenale virus (TATV), has been identified in field voles ( Microtus agrestis ) captured in different parts of England [ 60 , 61 ]. This virus is believed to be non-pathogenic in humans and rodents [ 62 ].…”
Section: Distribution Of Orthohantaviruses and The Diseases They Cmentioning
confidence: 99%
“…Later, TULV was also isolated from the vole samples collected in the central European countries [ 59 ]. A novel vole-associated hantavirus related to TULV and PUUV, Tatenale virus (TATV), has been identified in field voles ( Microtus agrestis ) captured in different parts of England [ 60 , 61 ]. This virus is believed to be non-pathogenic in humans and rodents [ 62 ].…”
Section: Distribution Of Orthohantaviruses and The Diseases They Cmentioning
confidence: 99%
“…In addition, SEOV RNA was detected in 2011 & 2012 in brown rats (Rattus norvegicus) that were epidemiologically linked to 2 HF cases [5]. Furthermore, a novel vole-associated Hantavirus related to TULV & PUUV, Tatenale virus (TATV), was identified in North West England in 2013 [6] and again in Northern England in 2017 [7].…”
Section: Main Textmentioning
confidence: 99%
“…The two strains were 94.1%, 91.3% and 90.6% similar at the nucleotide level, across the S, M and L segments, respectively. The original phylogenies of B41 and Kielder strains of TATV were based on <400bp fragments of the L and S or L segment, respectively [6,7]. figure 1A-B) showed that both the Norton-Juxta and Upton-Heath strains clustered with TATV.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The first orthohantavirus linked to HF in the UK was in 2011 when a novel strain of SEOV was isolated from wild rats captured on the farm of a patient with suspected HF [18]; SEOV was then detected in pet rats belonging to a patient with serologically confirmed HF in 2013 [19]. Furthermore, a novel vole-associated hantavirus related to TULV and PUUV-Tatenale virus (TATV)-was identified in field voles (Microtus agrestis) captured in northwest England in 2013 [20] and again in northern England in 2017 [21]. However, fragments of less than 400 nucleotides were retrieved for two of the three genomic segments, meaning that phylogenetic analysis of this virus was limited.…”
Section: Introductionmentioning
confidence: 99%